FEATURES OF INNOVATIVE ACTIVITY OF TEACHERS OF A HIGHER EDUCATIONAL INSTITUTION - Sabirova Umida Farxadovna (International Scientific and Current Research Conferences, 2023)
In modern conditions, it is important for teachers to quickly and mobilely perceive and apply new ideas, master modern approaches to teaching and educating students, and change their activities in accordance with the demands of education. The success of a teacher's activity is determined not only by the level of his professional and pedagogical skills, but also by the desire for self-development, self-improvement, which are based on the willingness to change oneself and change the situation around oneself. The effectiveness of this process is enhanced if teachers actively master innovations. In this article, the author analyzes in detail the theoretical foundations of the innovative activity of teachers of a higher educational institution.